Feestvierende Slovenen ter gelegenheid van 50 jaar Staatsmijnen. Uit de coll. Sloveense arbeidsmigranten in Limburg (1952)
Feestvierende Slovenen ter gelegenheid van 50 jaar Staatsmijnen. Uit de coll. Sloveense arbeidsmigranten in Limburg.